1 Peran Serikat Pekerja Nasional (SPN) DPC Kota Semarang dalam Memengaruhi Penetapan Kebijakan Upah Minimum Kota Semarang Tahun 2014 - Arsyad, M. Adnan; ., Yuwanto (Journal of Politic and Government Studies, 2017)
The issue of minimum wage is an interesting thing to study. At the end of each year the government issued a policy to set minimum wages that must be paid by the company to its workers. Surely this is not an easy thing to do. Consider that Parties unions demanding higher minimum wages because the wages have not been able to meet their daily lives. Meanwhile, the employer argued that the wage increase would increase the cost of production which led to the company becoming uncompetitive in the industrialized world.2In this study, researchers used a qualitative method that will generate descriptive data. To obtain research purposes appropriate data sources, researchers used purposive sampling techniques to conduct interviews with National Trade Union (SPN) Kota Semarang and Dewan Pengupahan Kota Semarang.SPN struggle to influence the process of determining the UMK Semarang carried through the political system and from outside the political system. The struggle through the political system is joined the Dewan Pengupahan Kota which had the authorities in determining the value of the Quality of Life (KHL) through a survey in five traditional markets in the city, namely Pasar Karangayu, Pasar Mangkang, Pasar Jatingaleh, Pasar Pedurungan and Pasar Langgar.Researchers recomend, for the creation of a favorable climate in the industrial world, governments need to make improvements from regulation to implementation. Because as the executor of a policy, the government should be able to act decisively. That way, the regulations that have been made can be implemented properly.